2007
DOI: 10.1093/molbev/msm005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Analysis of Nucleotide Variation of Oryza sativa and Its Wild Relatives: Severe Bottleneck during Domestication of Rice

Abstract: Varying degrees of reduction of genetic diversity in crops relative to their wild progenitors occurred during the process of domestication. Such information, however, has not been available for the Asian cultivated rice (Oryza sativa) despite its importance as a staple food and a model organism. To reveal levels and patterns of nucleotide diversity and to elucidate the genetic relationship and demographic history of O. sativa and its close relatives (Oryza rufipogon and Oryza nivara), we investigated nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
271
5
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(311 citation statements)
references
References 69 publications
27
271
5
8
Order By: Relevance
“…Further studies are required, whether of empirical or simulation nature, to investigate the sensitivity of LD estimates to these factors. Within the same species, wild populations usually harbor lower LD compared with their domesticated counterparts, as shown in barley (Caldwell et al, 2006), soybean (Lam et al, 2010), rice (Zhu et al, 2007), tomato (Arunyawat et al, 2007;Labate et al, 2009) and common bean (Rossi et al, 2009), reflecting changes in effective population size (Mather et al, 2007). In cultivated maize, for which LD was estimated based on large sequence data sets, the mean r 2 was 0.24 over a distance of 100 nucleotides and remained above 0.20 within 2 kb (Yan et al, 2009).…”
Section: Ld Patternsmentioning
confidence: 99%
“…Further studies are required, whether of empirical or simulation nature, to investigate the sensitivity of LD estimates to these factors. Within the same species, wild populations usually harbor lower LD compared with their domesticated counterparts, as shown in barley (Caldwell et al, 2006), soybean (Lam et al, 2010), rice (Zhu et al, 2007), tomato (Arunyawat et al, 2007;Labate et al, 2009) and common bean (Rossi et al, 2009), reflecting changes in effective population size (Mather et al, 2007). In cultivated maize, for which LD was estimated based on large sequence data sets, the mean r 2 was 0.24 over a distance of 100 nucleotides and remained above 0.20 within 2 kb (Yan et al, 2009).…”
Section: Ld Patternsmentioning
confidence: 99%
“…(ii) Further investigation of more cultivated strains, particular japonica, is needed to confirm this. Crops, including rice, have experienced strong artificial selection during domestication and their genetic diversity has significantly decreased -the so-called bottleneck effect [17,18]. [19,20].…”
Section: Comparison Of Sequences From Ancient and Modern Ricementioning
confidence: 99%
“…A recent investigation on domestication bottlenecks based on 10 neutral loci in rice indicated that domesticated rice maintains about 52.1% (p) of the variability found in its progenitor O. rufipogon [41]. In the MIR156b/c locus, however, only 8.9% diversity was maintained in the cultivated rice.…”
Section: Molecular Diversity and Selection Of Mir156b/cmentioning
confidence: 99%